EFFECT OF RESULTS AND ADMINISTRATIVE CONTROLS ON PERFORMANCE OF MANUFACTURING SMALL AND MEDIUM ENTERPRISES (SME’s) IN LAGOS STATE, NIGERIA - Mustapha Abdulrasaq (J-MACC, 2025)
The forms and nature of controls employed by managers to ensure an alignment of subordinate goal with overall organization goals is more critical to organization long term survival. However, given the rate of failures being reported as consequence of inappropriate use of management control across sectors, this study investigated the degree at which results and administrative control explain variation in Manufacturing SMESs performance in Lagos, Nigeria. Cross-sectional research approach was design to collect primary data, using structure questionnaire administered to randomly selected eight hundred and forty eight managers (848).The collected data was analyzed inferentially through Partial-Least Square Structural Equation Model(PLS-SEM).The results from the analysis revealed that: diagnostic use of control has positive impact on organization performance(β=0.372, P-value < 0.05); significant positive relation exists between interactive use of control and SMEs performance(β=0.317, P-value < 0.05) ;the use administrative control has significant impact on SMEs performance(β=0.214, P-value < 0.05) and social control also significantly explain variation in SMEs performance (β=0.214, P-value < 0.05).However, this study observed no significant relation between combined used of result and administrative control on performance. These findings have empirically confirmed the critical role of using results control diagnostically and interactively as well as other non-accounting-based controls to align subordinates’ objectives with organization goals and in effect improve performance. Therefore, SMEs organizations are encouraged to utilize these various forms of controls in their day-to-day activities to continually monitor their subordinate with minimal supervision costs. It is advisable for SMEs organization to deploy budget preparation beyond setting of targets by conducting variances analysis of the budget with actual report in a manner that critical performance variables that require urgent attentions are identified. They should also see the relevance of both administrative and social control in addressing organization activities that are not amenable to result control devices.